TRADISI PAMITAN HAJI PADA MASYARAKAT MUSLIM PURWOMARTANI KALASAN YOGYAKARTA: Kontestasi Agama dan Budaya - Yayan Suryana (Jurnal Sosiologi Reflektif, 2013)
This article discusses the farewell party of pilgrimage , a tradition thatis very popular in the Muslim community , especially in Yogyakarta, which was conducted before the person’s departure for pilgrimage.The study of the pilgrimage is an integral part of social science studiesthat intersect with religious reality. Not religious studies in the contextof “ theological aspects “ ?, but discusses the meaning of religion inthe lives of individuals. In addition, this article describes how socialinteractions contribute to the religious traditions. Through a phenomenologicalperspective, this paper generates a new concept in thestudy of pilgrimage and community treasures in its various aspects isreferred to as “syncretism in the pilgrimage.” This concept suggeststhat the farewell pilgrimage is not as described by the intellectualswho see Hajj farewell as tradition that implies the meaning of ritual.But the farewell pilgrimage is a tradition that is adjusted from time totime in accordance with the context of its time. This concept generatea view of social interaction and engagement-involvement in social lifeproduced simultaneously through the farewell pilgrimage tradition.Its doesn’t mean a syncretism in religion and cultural context thatimplies magical charges, but syncretism with social practices thatcan not be rationally disputed.